Assessment of left ventricular performance during percutaneous transluminal coronary angioplasty: a study by intravenous digital subtraction ventriculography. Issue 4 (April 1988) - Norell, M S; Lyons, J P; Gershlick, A H; Gardener, J E; Rothman, M T; Layton, C A; Balcon, R
Abstract : Left ventricular performance during percutaneous transluminal coronary angioplasty was assessed in 52 patients by intravenous digital subtraction ventriculography. After injection of contrast into the right atrium ventriculograms were obtained before and during balloon inflation. In 37 patients they were also obtained after the procedure. A 12 lead electrocardiogram was monitored throughout. During balloon inflation the left ventricular ejection fraction fell (from 73% to 57%) in all but one patient; the decreases in patients with single vessel or multivessel disease were similar. The fall in left ventricular ejection fraction during percutaneous transluminal coronary angioplasty of the left anterior descending artery (19%) was significantly greater than that during balloon inflation in the right coronary (10%) or circumflex (8%) coronary arteries. It also reduced anterobasal, anterior, and apical segmental shortening while right coronary percutaneous transluminal coronary angioplasty affected inferior and apical segments. In 33 (63%) patients the ST segment was altered during balloon inflation. The fall in left ventricular ejection fraction correlated significantly with the magnitude of both ST segment elevation (r = 0.637) and ST depression (r = 0.396). Left ventricular ejection fraction and regional wall motion returned to baseline values after the procedure. Balloon inflation during percutaneous transluminal coronary angioplasty produces considerable abnormalities of global and regional left ventricular performance and this indicates the presence of myocardial ischaemia, which may not be apparent on electrocardiographic monitoring. Intravenous digital subtraction ventriculography is useful for monitoring left ventricular performance during controlled episodes of coronary occlusion produced by balloon inflation.